2016
DOI: 10.3389/fpubh.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Awareness of Key Resources for Evidence-Informed Decision-making in Public Health: An Evaluation of a Webinar Series about Knowledge Translation Methods and Tools

Abstract: The National Collaborating Centre for Methods and Tools (NCCMT) has developed several resources to support evidence-informed decision-making – the process of distilling and disseminating best available evidence from research, context, and experience – and knowledge translation, applying best evidence in practice. One such resource, the Registry of Methods and Tools, is a free online database of 195 methods and tools to support knowledge translation. Building on the identification of webinars as a strategy to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(49 reference statements)
0
6
0
1
Order By: Relevance
“…11 Webinars also allow advanced registration and archival content. 12 Nevertheless, a successful webinar session is strongly dependent on the planning before the session. For our webinar, the topics of discussion were previously distributed among the panelists and discussed during a virtual practice session before the event.…”
Section: Discussionmentioning
confidence: 99%
“…11 Webinars also allow advanced registration and archival content. 12 Nevertheless, a successful webinar session is strongly dependent on the planning before the session. For our webinar, the topics of discussion were previously distributed among the panelists and discussed during a virtual practice session before the event.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Allen et al's (2013) research designed multiphase dissemination approaches that included multiday in-person training workshops, electronic information exchange modalities, and remote technical assistance. Yost et al noted that in Canada the National Collaborating Center for Methods and Tools (NCCMT) has established an online, searchable, and freely accessible collection of methods and tools to support knowledge translation in public health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results suggest that webinars are an effective method to improve participants' awareness of postgraduate programmes, such as the CST. This is supported by the study by Yost et al, which reported that participants sustained an improved awareness of methods and tools explored in webinars [15].…”
Section: Discussionmentioning
confidence: 52%